Pahon Cave, Gabon: New insights into the Later Stone Age in the African rainforest - Marie-Josée Angue Zogo; Isis Mesfin; Geoffroy de Saulieu; Wim Van Neer; Els Cornelissen; David Pleurdeau; Richard Oslisly (PLoS ONE, 2025)
Although the Later Stone Age as a distinctive techno-cultural phase has disappeared, forager groups in the African rainforest persist today. However, their origins remain poorly understood. The absence of stone tool production raises questions about the pace and processes of its decline and its relationship to the emergence or adoption of metallic tools. Archaeological sequences from the Middle and Late Holocene are particularly valuable for documenting the coexistence of diverse subsistence strategies and technologies within the Central African rainforest. In this context, the Pahon Cave sequence, in Gabon, spanning a period from 7,571 cal. BP to 2,523 cal. BP, provides an opportunity to study the evolution of stone tool production in the rainforest of the Ogooué Basin. This chronological range coincides with significant broader techno-cultural and environmental changes in Central Africa. This article provides a detailed description of the lithic industry for each layer, along with the identification of faunal remains, giving insight into the exploitation of rainforest resources and hunting practices. At Pahon Cave, our findings suggest that stone tool technology remained stable over time, at least until around 2,523 cal. BP. Furthermore, the technological characteristics of the lithic industry indicate no clear cultural affiliations. These features contribute highlighting a techno-cultural diversity during the Middle and Late Holocene Later Stone Age in Atlantic Central Africa.